PENGARUH KEPEMIMPINAN, KERJASAMA TIM DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI HOTEL FAIRMONT JAKARTA - Jamaludin Khalid; Novan Suwarno Ade Putra (LPPM Universitas Asa Indonesia, 2019)
Purpose- This research aims to know the influence of leadership, teamwork and discipline work against employee productivity Hotel Fairmont Jakarta. Design/methodology/approach- The data collected through the questionnaires are then measured by likert scale score with a total of 130 the respondent employees Hotel Fairmont Jakarta. Research using the method of double linear regression to analyze data. Data analysis tools that used this research are validity test, reliability test, classic assumption test (normality test, multicolinearity test, heteroscedasticity test, and linearity test), multilinear regression. While the hypotheses testing by F test, t test, partial correlation analysis and coefficient of determination (R2). Findings- The results showed a simultaneous leadership, teamwork and discipline work against work productivity. The leadership of the influential positive but not significant toward the work productivity. While teamwork and discipline work a positive and significant effect against work productivity. This result means teamwork and discipline work influenced positively against work productivity and the value is significantly to the productivity of employees. The leaders should pay more attention to the work in accordance with the disciplinary rules of procedures, enhance cooperation towards the better team against employees, and improve the overall results in terms of productivity. Productivity of employees become more efficient if receive effective training.